Alanine and Lysine Scans of the LL‐37‐Derived Peptide Fragment KR‐12 Reveal Key Residues for Antimicrobial Activity. (30th March 2018) - Gunasekera, Sunithi; Muhammad, Taj; Strömstedt, Adam A.; Rosengren, K. Johan; Göransson, Ulf
Abstract: The human host defence peptide LL‐37 is a broad‐spectrum antibiotic with immunomodulatory functions. Residues 18–29 in LL‐37 have previously been identified as a minimal peptide (KR‐12) that retains antibacterial activity with decreased cytotoxicity. In this study, analogues of KR‐12 were generated by Ala and Lys scans to identify key elements for activity. These were tested against a panel of human pathogens and for membrane permeabilisation on liposomes. Replacements of hydrophobic and cationic residues with Ala were detrimental for antibiotic potency. Substitutions by Lys increased activity, as long as the increase in cationic density did not disrupt the amphiphilic disposition of the helical structure. Importantly, substitutions showed differential effects against different organisms. Replacement of Gln5 with Lys and Asp9 with Ala or Lys improved the broad‐spectrum activity most, each resulting in up to an eightfold increase in potency against Staphylococcus aureus, Pseudomonas aeruginosa and Candida albicans . The improved analogues displayed no significant toxicity against human cells, and thus, KR‐12 is a tuneable template for antibiotic development. Abstract : Pinpointing critical positions : Alanine and lysine scans demonstrate that substituting amino acids 5 and 9 increases the activity of KR‐12 against human pathogens. Cationic substitutions in other positions lead to changes in specificity. Membrane‐permeabilisation assays show the same trends, which indicate membrane disruption as a mechanism of action, but peptides show no cytotoxic activity against human cells.